(untitled) (International Journal of Engineering and Computer Science, 2013)
Mobile Commerce is an evolving area of e-Commerce, where users can interact with the service providers through a mobile and wireless network, using mobile devices for information retrieval and transaction processing. M-Commerce services and applications can be adopted through different wireless and mobile networks, with the aid of several mobile devices. However, constraints of both mobile networks and devices influence their operational performance; therefore, there is a strong need for taking into consideration those constraints in the design and development phases of m-Commerce services and applications. Another important factor in designing m-Commerce services and applications is the identification of mobile users requirements. Furthermore, m-Commerce services and applications need to be classified based on the functionality they provide to the mobile users. This kind of classification results in two major classes: the directory and the transaction-oriented services and applications. This paper suggests a new approach for designing and developing m-Commerce services and applications. This approach relies on mobile users needs and requirements, the classification of the m-Commerce services and applications, as well as the current technologies for mobile and wireless computing and their constraints..